Diagnostic and treatment of infertility in outpatient clinic - Bączkowski, Tomasz; Kurzawa, Rafał (Przewodnik Lekarza/Guide for GPs, 2012)
Infertility affect 13-15% of couples in reproductive age. It is diagnosed after one year of unprotected regular intercourse. Infertility depends on female in 40-50%, on male in 30-40%, in 20% on both factors and in 10-15% the reason is not defined. Among female the reasons are: ovulation disorders, endometriosis, tubal factor, uterine and cervical disorders and immunological. Among men the most of the infertility cases depend on disorders of spermatogenesis and only 40-60% reasons are defined. Evaluation of ovulation by tests or ultrasound examination, ovulation induction or stimulation, improvement of sperm parameters and elimination of inflammation process in genital tract are first steps of infertility treatment. It is considered that such treatment can be led till maximum two years and then the couple should be sent to reproductive specialist.